1983
DOI: 10.1177/00220345830620090601
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Growth Responses of Oral Streptococci on Mixed Saliva or the Separate Submandibular and Parotid Secretions from Caries-active and Caries-free Individuals

Abstract: Growth of S. mutans on mixed or parotid saliva from CF individuals may be influenced by the availability of growth-supportive proteins or the inhibitory activity present in parotid saliva. A deficiency in growth-supportive proteins may explain the limited growth of S. sanguis on mixed or submandibular saliva from these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 10 publications
1
15
0
Order By: Relevance
“…In comparison to treatment with ethylene oxide, hydrogen peroxide or irradiation, conventional pressure filtration (as used in the present study) has the least effect on the composition of saliva without losing its capacity to support the growth of bacteria [Kalfas and Rundegren, 1991], However, because the concentration of almost all salivary antibacterial factors was affected by sterilization, glucosesupplemented sterilized saliva can be regarded only a model system which is relatively similar, but not identical, to the in vivo situation where, for example, bacterial inter actions are also important. Cowman et al [1983] observed better growth of S. mutans in saliva from caries-active donors than in saliva from caries-free subjects whereas the growth of S. salivarius was not influenced by the caries status of the donor. They also found that the susceptibility of salivary proteins to micro bial degradation differed between the two groups.…”
Section: Discussionmentioning
confidence: 71%
“…In comparison to treatment with ethylene oxide, hydrogen peroxide or irradiation, conventional pressure filtration (as used in the present study) has the least effect on the composition of saliva without losing its capacity to support the growth of bacteria [Kalfas and Rundegren, 1991], However, because the concentration of almost all salivary antibacterial factors was affected by sterilization, glucosesupplemented sterilized saliva can be regarded only a model system which is relatively similar, but not identical, to the in vivo situation where, for example, bacterial inter actions are also important. Cowman et al [1983] observed better growth of S. mutans in saliva from caries-active donors than in saliva from caries-free subjects whereas the growth of S. salivarius was not influenced by the caries status of the donor. They also found that the susceptibility of salivary proteins to micro bial degradation differed between the two groups.…”
Section: Discussionmentioning
confidence: 71%
“…64 While quantitative studies of salivary composition and caries activity have been inconclusive, there is evidence that similar proteins in saliva from caries-active and caries-free individuals may have different levels of biological activity. [65][66][67][68] Our laboratory found no differences in parotid saliva flow rates and buffer capacity in caries active versus caries-free young adults, although the caries-active group had slightly, but significantly, higher parotid salivary potassium and chloride concentrations. 69 Saliva regulates the plaque pH by minimizing the pHlowering effects of sugars, 47 whereas increasing the flow of saliva by chewing wax or a sugar free gum results in an increase in plaque pH.…”
Section: Salivary Composition and Cariesmentioning
confidence: 99%
“…Comparison of sequences indicated the strong likelihood that the small peptides were derived from the salivary histatins (Troxler et al, 1990), acid proline-rich proteins (Hay et al, 1988), basic proline-rich proteins (Kauffman et al, 1991), and statherins (Jensen et al, 1991) via the action of proteases present in the salivary glands or ducts. In addition to the likelihood of host-mediated proteolysis, Streptococcus mitis (Hiraoka et al, 1986) and S. sanguis (Cowman et al, 1983;Rogers et al, 1988) produce arginine aminopeptidases. In the case of the S. sanguis aminopeptidase, the enzyme was shown to liberate arginine from short peptides of various lengths, including tetra-, penta-, and hexapeptides.…”
Section: (C) Regulation Of the S Mutans F-atpase Operonmentioning
confidence: 99%